Immune-Based Therapies for Traumatic Brain Injury: Insights from Pre-Clinical Studies - Machado, Caroline A.; Silva, Ana Cristina Simões e; de Miranda, Amanda Silva; Cordeiro, Thiago Macedo e; Ferreira, Rodrigo Novaes; de Souza, Leonardo Cruz; Teixeira, Antônio Lúcio; de Miranda, Aline Silva (Current Medicinal Chemistry, 2020)
Traumatic Brain Injury (TBI) is a major public health problem. It is the leading cause of death and disability, especially among children and young adults. The neurobiology basis underlying TBI pathophysiology remains to be fully revealed. Over the past years, emerging evidence has supported the hypothesis that TBI is an inflammatory based condition, paving the way for the development of potential therapeutic targets. There is no treatment capable to prevent or minimize TBIassociated outcomes. Therefore, the search for effective therapies is a priority goal. In this context, animal models have become valuable tools to study molecular and cellular mechanisms involved in TBI pathogenesis as well as novel treatments. Herein, we discuss therapeutic strategies to treat TBI focused on immunomodulatory and/or anti-inflammatory approaches in the pre-clinical setting.
Keywords: inflammation